The Political Nature of Digital Cultural Heritage - McCrary, Quincy (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2011)
Collecting organizations such as libraries and museums are vehicles for shifting paradigms of knowledge and power. Digital technologies are also implicated with historical transformations in language, society, and culture. To discuss the digital is to engage simultaneously with an impressive array of simulacra, instantaneous communication, ubiquitous media, and global interconnectedness (Cameron & Kenderdine, 2007). Digital cultural heritage can be viewed as a political concept and practice, the relations between communities and heritage institutions as mediated through technologies, the reshaping of social, cultural, and political power in relation to cultural organizations made possible through communication technologies, and the representation and interpretation of digital cultural heritage. The following paper will address each of these concerns, outlining current scholarship on the topic and critically engaging with the content.